Developing an E-Module on Economics Based on Education for Sustainable Development to Enhance High School Students' Critical Thinking - Ana luthfiyah; Waspodo Tjipto Subroto; Norida Canda Sakti (Universitas Sebelas Maret, 2025)
This study developed an economics e-module aligned with Education for Sustainable Development (ESD) to respond to the urgent need for innovative learning resources that foster students’ critical thinking in facing sustainability challenges. The e-module was designed using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), created with Canva, and presented in flipbook format via Heyzine. Findings confirmed a significant advancement in students’ critical thinking skills, with a Paired Sample t-Test result of Sig. (2-tailed) < 0.001 and an Independent Sample t-Test result of 0.040. The experimental class attained higher mean N-Gain score (0.64, moderate) contrasted to the control class (0.53). Students also rated the e-module very positively (90%, excellent). These results reveal that the ESD-based economics e-module is practical, effective, and contributes to the enhancement of high school students’ critical thinking abilities.